2006
DOI: 10.1088/0022-3727/39/22/018
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ambient pressure and laser fluence on the temporal evolution of 426.7 nm CII line in laser-blow-off of multilayered LiF-C thin film

Abstract: The time and space resolved emission profiles of the CII line from the laser-blow-off (LBO) plumes of multilayered LiF-C thin film have been investigated using a laser-induced forward transfer technique. The evolution features of the 426.7 nm line were studied in different ambient environments ranging from high vacuum to 3 mbar of argon pressures and at various fluences of the ablating laser. It was found that many features of the plasma plume generated by the LBO method resemble that of plumes created in conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
15
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 35 publications
5
15
0
Order By: Relevance
“…4,6 Only the main features and additional parts of the setup are summarized here. In order to study the plume propagation dynamics for close and far distances from the target and the effect of electrical probe on the characteristic plume expansion, our present experimental setup is equipped with both TLP assembly and time and space resolved OES diagnostics.…”
Section: Methodsmentioning
confidence: 99%
“…4,6 Only the main features and additional parts of the setup are summarized here. In order to study the plume propagation dynamics for close and far distances from the target and the effect of electrical probe on the characteristic plume expansion, our present experimental setup is equipped with both TLP assembly and time and space resolved OES diagnostics.…”
Section: Methodsmentioning
confidence: 99%
“…A detailed description of experimental setup has been reported in our previous papers [8,9]. Only the main features and additional part of the setup are summarized here.…”
Section: Methodsmentioning
confidence: 99%
“…The optical emission spectroscopic technique of LBO plume [8][9][10] has revealed that expansion feature of plume is highly dependent on the experimental conditions and varies according to the ambient environment and laser fluence. But this technique cannot provide information regarding the influence of experimental parameters on the structure of the plasma plume.…”
mentioning
confidence: 99%
“…The present experimental setup is similar to the one described in our recent papers. 15,17 Only the main features and additional part of the setup are summarized here.…”
Section: Methodsmentioning
confidence: 99%
“…In the case of LBO, plasma plume ͑Li͒ consists of mainly neutral and singly ionized atoms 5,[12][13][14][15] and hence recombination processes could lead to the enhancement of neutral emission lines. Therefore, it is interesting to see behavior of LBO generated species ͑specially neutral species͒ in the presence of transverse magnetic field.…”
Section: Introductionmentioning
confidence: 99%